Numerical model of alluvial terrace and valley evolution applied to the Quaternary of Central Amazonia - Prado, Ariel Henrique do (2020)
The study of the mechanisms which shape the central Amazonia alluvial landscapes in the long term is of great relevance for the reconstruction of the past drainage systems and biogeographical patterns in the region. Current conceptual models for the Quaternary are based on paleogeographic interpretations of the vast alluvial terrace systems found in the region and on the role of external forcings, such as climate change, eustatic variation and neotectonics. In that context, evaluating, from a quantitative perspective, the interactions between alluvial dynamics and those external controls is key to constraint the interpretation of the morphological elements and sedimentary deposits. Therefore, the aim of this dissertation is to present a new numerical model capable of quantitatively testing hypotheses and conceptual models concerning the evolution of the great alluvial plains in Central Amazonia during the Quaternary. The model operates at a spatial of 10 5 km 2 and a temporal scale of 10 5 years, and presents a novel approach to simulate the lateral erosion of channel banks, coupled with a conventional model of erosion and deposition of sediments on channel beds. Scenarios were tested which simulate the modern configuration of the region containing the Solimões river and its tributary Japurá River, but with altered rainfall rates, rates of lateral erosion, base-level variation, sediment input and subsidence of specific areas in the grid to simulate the development of grabens. The results reveal that lateral erosion in an essential mechanism not only for the formation of alluvial plains and widening of valleys but also for the shape of the river long profiles, thus significantly altering the landscape evolution. In-valley incisional and aggradational processes resulted from three different mechanisms: base-level variation, changes in rainfall rate and shifts in the trunk river position, which modified the local base level for the tributaries. In the case of in-valley aggradation due to base-level rise of a drop in the rainfall rate, the trunk river, with great sediment flux, is capable of infilling the new accommodation space. Smaller tributaries, on their turn, cannot respond to the elevation of the trunk river alluvial plain and develop ria lakes. An important effect recognized in the model is an increase in the rate of valley widening by lateral erosion during deposition and aggradation, since the augmented avulsion rates at that stage result in a higher probability of valley margin erosion. The graben formation scenario reveals that when these tectonic features occur in the trunk river valley, they are rapidly filled and their margins are reworked by erosion, thus leaving no evidence of their presence in the landscape surface. Grabens developed on higher terraces, on the other hand, result in preserved morphological elements. As a whole, these results reveal processes and relations that have not been considered in current conceptual models, while enabling quantitative testing of the hypotheses concerning the paleogeography and the role of external forcings in the evolution of large alluvial plains.